Valorisation of Waste Tires by Pyrolysis in the Republic of Congo - Ulrich Berry; Smael Magloire Elombo Motoula; Réné Evrard Josué Samba (Asian Journal of Science, Technology, Engineering, and Art, 2026)
The pyrolysis of waste tires represents an effective strategy for simultaneous energy recovery and waste reduction, yet further empirical characterization of the resulting pyrolytic oil is needed to assess its suitability as an alternative fuel. This study aims to obtain pyrolytic oil from end-of-life tires and analyze its main physical characteristics to evaluate its potential for energy applications. The oil produced by pyrolysis exhibits a density of 769.4 kg/m³, a specific gravity of 0.7694, a low kinematic viscosity of 1.5 cSt, and a slightly acidic pH of 4, values that are consistent with those reported in the literature. These characteristics indicate a high proportion of light hydrocarbons, suggesting that the oil is suitable for use as a fuel or as a fuel additive. Observed variations compared with other studies highlight the influence of tire composition and pyrolysis conditions on the quality and properties of the obtained oil, underlining the importance of process optimization. Overall, the findings confirm that tire pyrolysis is a promising method for energy recovery from waste tires, providing a sustainable pathway for hydrocarbon production while contributing to improved solid waste management and resource valorization.